FORECASTING AND EXPERIMENTAL DETERMINATION OF DESTRUCTION IMPURITIES AND IN THE PHARMACEUTICAL COMPOSITION OF THE HYPOTENSIVE ACTION - E. V. Kompantseva; A. V. Babyak; Y. V. Mudretsova; A. A. Glushko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Determination results of impurities verapamil hydrochloride and lisinopril dihydrate using computer modeling and HPLC coupled with mass spectrometry (HPLC-MS) reported in this article. Prediction and calcu-lation of the thermodynamic characteristics of the substances carried by the method of RM1 and programs HyperChem. Mass spectrometric analysis was performed on a quadrupole mass analyzer in the recording mode of the positive ions within the range m / z 100-1000. The study found that described in the regulations extrane-ous verapamil and lisinopril are the products of degradation of materials. Prediction of degradation products of lisinopril dihydrate fully confirmed the data of the ion current chromatograms and mass spectra of the substanc-es. However, in the case of verapamil simulation results coincided with the degradation products by HPLC-MS analysis for two of the four predicted substances